Corrosion mechanism of Ti/IrO2-RuO2-SiO2 anode for oxygen evolution in sulfuric acid solution. (1st July 2020) - Liu, Bao; Ma, Baozhong; Chen, Yongqiang; Wang, Chengyan
Highlights: Corrosion mechanism of the compact IrO2 -RuO2 -SiO2 coating for OER was investigated. Electrolysis process of the anode was divided into four stages. Electrolysis time dependence of surface morphology was obtained. Coating dissolution and local oxidation of Ti base lead to the failure of the anode. Abstract: Corrosion mechanism of the compact IrO2 -RuO2 -SiO2 coating for oxygen evolution reaction (OER) in sulfuric acid solution was revealed by physical characterization and electrochemical measurements. According to the variations of the cell potential, the electrolysis process of the anode was divided into four stages, including penetration stage, stable stage, slow deactivation stage and sharp deactivation stage. The mechanism for each stage was illustrated. The synergistic effect of the large dissolution of the active components and the localized oxidation of the Ti substrate is regarded as the main reason for the failure of the Ti/IrO2 -RuO2 -SiO2 anode.